Engaging Learners via Live Online Learning - Taylor Nash; Megan S. Cantrell (EDIS, 2021)
The explosion of virtual training and education has created opportunities for interactions far beyond what is available in a face-to-face environment. However, easier access to individuals comes with unforeseen challenges in creating an environment that fosters genuine engagement. This new publication includes engagement strategies for the Extension environment as well as the virtual classroom of traditional education. Written by Taylor Nash and Megan Cantrell; 3 pp. https://edis.ifas.ufl.edu/wc395